Combating Internet Fraud through Operative-Search Measures - Shaisultanov, Samat; Akimzhanov, Talgat; Abdrakhmanov, Boris; Bazarlinova, Ardak; Bazarlinova, Aida (Law, State and Telecommunications Review, 2024)
[Purpose] Currently, the rapid development of Internet technologies leads to an increase in the number of fraud-related offences, which requires effective ways to prevent and detect them. The purpose of the study was to determine the essence, features, and problems of operative-search counteraction to Internet fraud. [Methodology] The methodological basis of the study was formal and logical, system and structural analysis, ranking, and generalisation, which allowed: identifying current trends and indicators of cybercrime; clarifying the concept and content of operative-search counteraction to fraud on the Internet; conducting a legal analysis of the criminal law norms of the Republic of Kazakhstan and the EU in the field of fraudulent cybercrime; investigating the processes for identifying and preventing fraudulent cybercrimes by law enforcement institutions; highlighting certain aspects of protection against Internet fraud; analysing individual criminological strategies for preventing fraudulent crime using the Internet; identifying the features of interaction between government agencies in the field under study; considering key problematic issues of preventing fraudulent offences on the Internet and ways to solve them; revealing the prospects for the development of methods to combat fraudulent cybercrimes. [Findings] The main results of the study were the definition of modern approaches to the interpretation of the concepts of “cybercrime,” “fraud,” “operative-search counteraction”; consideration of the regulatory support of Kazakhstan and the member states of the EU in the field of combating Internet fraud; clarification of the issue of criminal identification of fraudulent cybercrimes; clarification of practical aspects of operative-search measures to counteract fraudulent offences on the Internet; generalisation of possibilities for improving operative-search counteraction to fraud committed via the Internet. The significance of the results lies in the provision of practical recommendations regarding the concept and methods of operative-search counteraction to Internet fraud.